Determination of Effective Functional Monomer and Solvent for R(+)-Cathinone Imprinted Polymer Using Density Functional Theory and Molecular Dynamics Simulation Approaches - Andrian Saputra; Karna Wijaya; Ria Armunanto; Lisa Tania; Iqmal Tahir (Indonesian Journal of Chemistry, 2017)
Determination of effective functional monomer and solvent for R(+)-cathinone imprinted polymer through modeling has been done using density functional theory (DFT) and molecular dynamics (MD) simulation approaches. The selection criteria of the best monomer and solvent are based on the classical potential energy (ΔEMM) from molecular dynamics simulation and confirmed further by quantum potential energy (ΔEDFT) from DFT calculation. The DFT calculation was performed in B3LYP exchange-correlation functional within the 6-31G(d) basis set of function including Polarizable Continuum Model (PCM) solvation effect. From this research, it is obtained that N,N’-methylene bis acrylamide and chloroform are respectively the best candidates for effective functional monomer and solvent, for the synthesis of R(+)-cathinone imprinted polymer.